PUPINTAR (POP-UP BOOK PINTAR) SEBAGAI MEDIA UNTUK MEMBANTU MENINGKATKAN PEMAHAMAN KONSEP IPAS SISWA SEKOLAH DASAR - Fadilah, Nurul; Ira Restu Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted to develop the PUPINTAR (Pop-up Pintar) instructional media, which presents learning materials on Indonesia’s cultural diversity for fourth-grade students. The development process adopted the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study involved a sample of 36 fourth-grade elementary school students. Data were gathered through interviews, observations, questionnaires, and tests, and were analyzed using both qualitative and quantitative approaches. The mean feasibility rating provided by expert validators was 95%, falling into the “Highly Feasible” category. The practicality of the PUPINTAR media was rated as “Highly Practical,” with teacher responses scoring 97.6% and student responses 90.5%. Effectiveness testing using the N-Gain method resulted in a “Moderate” classification, with an average score of 0.65 and a percentage score of 65%, categorized as “Fairly Effective”.